Accounting for the middle: motivations, extent, and limitations of middle managers' earnings management - Sebastian Wagener (Journal of Business Economics, 2023)
The accounting process is complex and prone to interference from the various parties involved. Using middle managers, we examine one of the unknowns of this process. They are able to influence earnings long before top executives can, but their actions are virtually untraceable in consolidated financial statements. We gather survey data from 77 middle managers to shed light on their motivations, the extent of their earnings management, and the relevant limitations of the associated practices. Our results indicate that there is no uniform motivation that drives all of these managers equally. The spectrum of reported motivations includes meeting targets, smoothing earnings, and reducing future expectations. Despite this diversity, a large majority of the surveyed middle managers state that they manage earnings substantially but mostly downwards. To this end, they employ both accounting actions, such as adjustments to provisions, and real actions, such as transaction shifts. In the opinions of the middle managers in this sample, the factors that most limit their discretion are auditors and internal controls. The results also reveal the influence of superiors on middle managers' practices throughout the accounting process.
Keywords: M41; G30; 650; Earnings management; Middle management; Earnings quality; Survey